Force Sensitivity in Saccharomyces cerevisiae Flocculins - Chan, Cho X. J. (mSphere, 2016)
Many fungal adhesins have short, β-aggregation-prone sequences that play important functional roles, and in the Candida albicans adhesin Als5p, these sequences cluster the adhesins after exposure to shear force. Here, we report that Saccharomyces cerevisiae flocculins Flo11p and Flo1p have similar β-aggregation-prone sequences and are similarly stimulated by shear force, despite being nonhomologous. Shear from vortex mixing induced the formation of small flocs in cells expressing either adhesin. After the addition of Ca(2+), yeast cells from vortex-sheared populations showed greatly enhanced flocculation and displayed more pronounced thioflavin-bright surface nanodomains. At high concentrations, amyloidophilic dyes inhibited Flo1p- and Flo11p-mediated agar invasion and the shear-induced increase in flocculation. Consistent with these results, atomic force microscopy of Flo11p showed successive force-distance peaks characteristic of sequentially unfolding tandem repeat domains, like Flo1p and Als5p. Flo11p-expressing cells bound together through homophilic interactions with adhesion forces of up to 700 pN and rupture lengths of up to 600 nm. These results are consistent with the potentiation of yeast flocculation by shear-induced formation of high-avidity domains of clustered adhesins at the cell surface, similar to the activation of Candida albicans adhesin Als5p. Thus, yeast adhesins from three independent gene families use similar force-dependent interactions to drive cell adhesion. IMPORTANCE The Saccharomyces cerevisiae flocculins mediate the formation of cellular aggregates and biofilm-like mats, useful in clearing yeast from fermentations. An important property of fungal adhesion proteins, including flocculins, is the ability to form catch bonds, i.e., bonds that strengthen under tension. This strengthening is based, at least in part, on increased avidity of binding due to clustering of adhesins in cell surface nanodomains. This clustering depends on amyloid-like β-aggregation of short amino acid sequences in the adhesins. In Candida albicans adhesin Als5, shear stress from vortex mixing can unfold part of the protein to expose aggregation-prone sequences, and then adhesins aggregate into nanodomains. We therefore tested whether shear stress from mixing can increase flocculation activity by potentiating similar protein remodeling and aggregation in the flocculins. The results demonstrate the applicability of the Als adhesin model and provide a rational framework for the enhancement or inhibition of flocculation in industrial applications.